2022
DOI: 10.3389/fpubh.2022.979933
|View full text |Cite
|
Sign up to set email alerts
|

Molecular classification of human papillomavirus-positive cervical cancers based on immune signature enrichment

Abstract: BackgroundHuman papillomavirus-positive (HPV+) cervical cancers are highly heterogeneous in clinical and molecular characteristics. Thus, an investigation into their heterogeneous immunological profiles is meaningful in providing both biological and clinical insights into this disease.MethodsBased on the enrichment of 29 immune signatures, we discovered immune subtypes of HPV+ cervical cancers by hierarchical clustering. To explore whether this subtyping method is reproducible, we analyzed three bulk and one s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
1
0
Order By: Relevance
“…From pathway enrichment analysis, we found that early stages of invasive CeCa differed from their non-invasive precursor lesions in marked up-regulation of innate immunity pathways, particularly antiviral mechanisms mediated by DNA-sensors, and involvement of IFN-stimulated, pro-inflammatory, as well as DDR-related genes. This probably implies that overstimulation of protective mechanisms in early periods may be one of the triggers and contributors of invasion; at subsequent stages this could become manifest in the form of an immune-active but chronically inflamed and exhausted molecular subtype (43)(44)(45). Relatedness of the DDR-associated processes and "heating-up" the immune TME has also been underscored by some researchers (42,(46)(47)(48).…”
Section: Discussionmentioning
confidence: 99%
“…From pathway enrichment analysis, we found that early stages of invasive CeCa differed from their non-invasive precursor lesions in marked up-regulation of innate immunity pathways, particularly antiviral mechanisms mediated by DNA-sensors, and involvement of IFN-stimulated, pro-inflammatory, as well as DDR-related genes. This probably implies that overstimulation of protective mechanisms in early periods may be one of the triggers and contributors of invasion; at subsequent stages this could become manifest in the form of an immune-active but chronically inflamed and exhausted molecular subtype (43)(44)(45). Relatedness of the DDR-associated processes and "heating-up" the immune TME has also been underscored by some researchers (42,(46)(47)(48).…”
Section: Discussionmentioning
confidence: 99%
“…Overstimulation of protective mechanisms in early periods may be one of the triggers and contributors of CeCa invasion. At the same time, at later, advanced stages this could become manifest in the form of a widely documented immune-active but chronically inflamed and exhausted molecular subtype [6,10].…”
Section: Transcriptomebased Analysis Of Cell Population Compositionmentioning
confidence: 99%